Plastic pollution in the Labrador Sea: An assessment using the seabird northern fulmar Fulmarus glacialis as a biological monitoring species. (February 2018) - Avery-Gomm, Stephanie; Provencher, Jennifer F.; Liboiron, Max; Poon, Florence E.; Smith, Paul A.
Abstract: Plastic is now one among one of the most pervasive pollutants on the planet, and ocean circulation models predict that the Arctic will become another accumulation zone. As solutions to address marine plastic emerge, is essential that baselines are available to monitor progress towards targets. The northern fulmar ( Fulmarus glacialis ), a widely-distributed seabird species, has been used as a biological monitor for plastic pollution in the North Sea, and could be a useful monitoring species elsewhere. We quantified plastic ingested by northern fulmars from the southeastern Canadian waters of the Labrador Sea with the objective of establishing a standardized baseline for future comparisons. Over two years we sampled 70 fulmars and found that 79% had ingested plastic, with an average of 11.6 pieces or 0.151 g per bird. Overall, 34% of all fulmars exceeded the Ecological Quality Objective for marine litter, having ingested > 0.1 g of plastic. Highlights: Plastic is now one of the most pervasive pollutants on the planet. The seabird, northern fulmar, is a useful biological monitor for plastic pollution. To address a key data gap, we examine 70 fulmars from the Labrador Sea in 2014–2015. We found 79% of birds had ingested plastic. On average, fulmars ingested average of 11.6 pieces or 0.151 g per bird. Plastic ingestion exceeds targets developed in the North Sea.